Dynamic release of neuronal extracellular vesicles containing miR-21a-5p is induced by hypoxia - Korvenlaita, Nea; Gómez-Budia, Mireia; Scoyni, Flavia; Pistono, Cristiana; Giudice, Luca; Eamen, Shaila; Loppi, Sanna; de Sande, Ana Hernández; Huremagic, Benjamin; Bouvy-Liivrand, Maria; Heinäniemi, Merja; Kaikkonen, Minna U; et al. (Journal of extracellular vesicles, 2023)
Hypoxia induces changes in the secretion of extracellular vesicles (EVs) in several non-neuronal cells and pathological conditions. EVs are packed with biomolecules, such as microRNA(miR)-21-5p, which respond to hypoxia. However, the true EV association of miR-21-5p, and its functional or biomarker relevance, are inadequately characterised. Neurons are extremely sensitive cells, and it is not known whether the secretion of neuronal EVs and miR-21-5p are altered upon hypoxia. Here, we characterised the temporal EV secretion profile and cell viability of neurons under hypoxia. Hypoxia induced a rapid increase of miR-21a-5p secretion in the EVs, which preceded the elevation of hypoxia-induced tissue or cellular miR-21a-5p. Prolonged hypoxia induced cell death and the release of morphologically distinct EVs. The EVs protected miR-21a-5p from enzymatic degradation but a remarkable fraction of miR-21a-5p remained fragile and non-EV associated. The increase in miR-21a-5p secretion may have biomarker potential, as high blood levels of miR-21-5p in stroke patients were associated with significant disability at hospital discharge. Our data provides an understanding of the dynamic regulation of EV secretion from neurons under hypoxia and provides a candidate for the prediction of recovery from ischemic stroke.
Keywords: neuron; hypoxia; miR-21a-5p; MicroRNAs; Neurons; lidé; biomarkers; Extracellular Vesicles; extracellular vesicle; biologické markery; extracelulární vezikuly; neurony; Biomarkers; mikro RNA; ischemic stroke; Humans